2009
DOI: 10.1080/01421590802208891
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from an adolescent simulated patient educational program: Five years of experience

Abstract: Teachers, students and adolescent SPs have highly valued the adolescent SP program over the past five years.The program has been changed on the basis of the lessons learned and has become mature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…answer call in the middle of OSCE) as part of SP performance (12). Maastricht Assessment of Simulated Patients (MaSP) is commonly used as an instrument to evaluate SP performance (13)(14)(15). Meanwhile, video recording and written feedback or scoring were used as strategies to evaluate SP performance (15,16).…”
Section: Evaluation Of Sp's Performancementioning
confidence: 99%
See 2 more Smart Citations
“…answer call in the middle of OSCE) as part of SP performance (12). Maastricht Assessment of Simulated Patients (MaSP) is commonly used as an instrument to evaluate SP performance (13)(14)(15). Meanwhile, video recording and written feedback or scoring were used as strategies to evaluate SP performance (15,16).…”
Section: Evaluation Of Sp's Performancementioning
confidence: 99%
“…A study on using SP to teach students on managing difficult patients found that SP activity had added realism to the learning experience (mean = 4.42) while some students even felt stressed and emotionally involved when interacting with the SP (17). When compared between longitudinal SP programme and single case SP programme, students scored SP in the longitudinal programme as more authentic and more like real patient compared to SP in single case programme (p = 0.00) (13). However, the validity in assessing candidates' empathy during SP encounter was considered to be not real (18).…”
Section: Authenticity Of Sp Role Playmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these studies, 5 were conducted in the USA [17][18][19][20][21] or Canada [22][23][24][25][26] while one study was a systematic review from multiple countries [12]. The remaining four studies originated in New Zealand [27], Africa [28] and The Netherlands [29,30]. Eleven studies identified the health professional group to which the learner belonged.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…SP participant numbers ranged from four to twenty-four. Ten studies either did not specifically identify gender of the children or adolescent SPs or employed both males and females [12, 17-21, 24-26, 28], three studies focused solely on females [22,23,27] and two studies included a small number of males through convenience rather than planning [29,30]. SPs were recruited from an existing database, following contact with a local community theatre or drama group or from faculty willing to involve their own children.…”
Section: Description Of Studiesmentioning
confidence: 99%